Economic Feasibility of Embankment Construction with a Polder System for Optimizing Sustainable Palm Oil Cultivation - Hermantoro Hermantoro; Fahmi W Kifli; Rolly Marta; Wandha Atmaka Aji; Risca Permatasari Nirfrizal (The University of Lampung, 2025)
Lowland areas in oil palm plantations is often flooded due to river overflows and high rainfall, which results in reducing oil palm productivity. This research aims to analyze the feasibility of investing in building embankments with a polder system to optimize lowland areas for sustainable oil palm cultivation. The research method uses a quantitative descriptive approach with financial analysis based on NPV, IRR, PP, PI, BCR and BEP parameters. The research results show that the polder system increases land productivity from 60–61% utilization to 100%, with an optimal projection of 136 trees/ha. Even though investment costs increased from IDR 11.8 billion to IDR 14.4 billion, the financial feasibility analysis resulted in a positive NPV of IDR 964,200,861, IRR 22.20% (> 20% ​​discount), PP 10 years, PI 2.17 > 1, BCR 1.21 > 1 and BEP achieved in 10 years. In conclusion, building embankments with a polder system is financially and technically feasible, increasing productivity while reducing the risk of flooding. Recommendations include regular monitoring of the polder system and integration with sustainable cultivation practices